How does website quality and trust towards website influence online purchase intention? - Rukhsana Kouser; Ghulam Shabbir Khan Niazi; Haroon Bakari (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
Online shopping is gaining popularity in Pakistan but the research on its determinants is scarce. The main purpose of this study is to explore what factors are important in developing online purchase intention of Pakistani youth interested in shopping through the internet. The data were collected through questionnaires using convenience sampling technique from 502 mainly young respondents of Pakistan. The theoretical model of the current study is developed on the theory of planned behavior (TPB). To test hypotheses, structural equation modeling (with maximum likelihood approach) has been used through AMOS software. The results suggest that website quality and trust in e-commerce social websites are positively related to online purchase intention. Users' attitude towards online shopping partially mediated the links. This study has important implication for new e-vendors such that in order to promote online shopping, they need to improve quality features of website and enhance users' trust.
Keywords: 330; customer service; website quality; normative influence; online shopping; online purchase intention; trust towards website